Pengaruh Solvabilitas Dan Laba Operasi Terhadap Kecenderungan Audit Delay Dengan Struktur Kepemilikan Manajerial Dan Ukuran Perusahaan Sebagai Pemoderasi - Dhelia Dayu Anasthasia; Gede Adi Yuniarta; Desak Nyoman Sri Werastuti (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract This study aims to prove (1) the effect of solvency on audit delay, (2) the effect of operating profit on audit delay, (3) managerial ownership structure can moderate the effect of solvency on audit delay, (4) managerial ownership structure can moderate the effect of operating profit. has an effect on audit delay, (5) firm size can moderate the effect of solvency on audit delay, and (6) firm size can moderate the effect of operating profit on audit delay. To achieve the research objectives, the research design used is causal quantitative by using secondary data obtained from the company's annual financial statements. The population of this research is all companies in the Property, Real Estate and Building Construction sector on the Indonesia Stock Exchange as many as 65 companies. The sampling technique in this study used purposive sampling with a total sample of 35 companies. The data analysis technique used is moderated regression analysis. The results show that (1) solvency has a positive effect on audit delay, (2) operating profit has a negative effect on audit delay, (3) managerial ownership structure can moderate the effect of solvency on audit delay, (4) managerial ownership structure can moderate the effect of earnings. operations affect audit delay, (5) firm size can moderate the effect of solvency on audit delay, (6) firm size can moderate the effect of operating profit on audit delay. Keywords : solvency, operating profit, managerial ownership, firm size, audit delay